Should We Extend the Role of Private Social Expenditure? - Mark Pearson; John P. Martin (Institute for the Study of Labor (IZA), 2005)
Some people make great claims about the advantages to be gained from greater reliance on the private sector for the provision of social protection. Many of the claims for great macroeconomic advantages do not stand up to scrutiny. However, there is some reason to hope that private provision might promote microeconomic efficiency and services which are more responsive to consumer preferences than those provided by a single monopoly public sector provider. Drawing on examples from recent OECD country experiences with private health insurance, care for children and the elderly, and private pension provision, three main conclusions can be drawn. First, opening provision to a diversity of providers has often promoted more choice and innovation. Second, however, efficiency gains have often been limited. This is due to a number of inter-related reasons: (a) Individualisation of packages of services is expensive. (b) In order to ensure adequate coverage of the population, crosssubsidisation of particular groups of people is often mandated on providers, reducing costcompetition and diversity of choice. (c) Informational asymmetries (how good is this childcare which I cannot personally monitor, or this health care package which I am not technically able to assess?) cannot be overcome without extensive regulation, which has the effect of limiting innovation and competition. (d) The fiscal incentives necessary to stimulate private provision are high, and have welfare costs of their own. Third, and related to this last point, the distributional effects of private provision raise significant social problems. Private financing and provision of social benefits is not a magic wand; waving it in the social protection field will not mean that the economy and voters will be freed from some great deadweight that has been dragging them down. Nevertheless, the private sector can sometimes deliver either a slightly cheaper, slightly more varied or slightly more flexible system of social protection.
Keywords: H42; H11; H53; H51; L33; 330; private social protection; private health insurance; child care; long-term care for the frail elderly; private pensions; efficiency; choice